High-efficiency organic solar cells processed from a real green solvent. Issue 2 (5th December 2022) - Pang, Shuting; Chen, Zhili; Li, Junyu; Chen, Yuting; Liu, Zhitian; Wu, Hongbin; Duan, Chunhui; Huang, Fei; Cao, Yong
Abstract : High-efficiency organic solar cells processed from anisole, a real green and eco-compatible solvent recommended by the United Nations, are achieved by introducing the polar B–N covalent bond into the conjugated backbone of the polymer donor. Abstract : The fabrication of organic solar cells (OSCs) depends heavily on the use of highly toxic chlorinated solvents, which are incompatible with industrial manufacturing. The reported alternative solvents such as non-halogenated aromatic hydrocarbons and cyclic ethers are also not really "green" according to the "Globally Harmonized System of Classification and Labelling of Chemicals" of the United Nations. Therefore, processing from real green solvents such as water, alcohols, or anisole will constitute a big breakthrough for OSCs. However, it is fundamentally challenging to obtain high-performance photovoltaic materials processable from these solvents. Herein, we propose the incorporation of a B–N covalent bond, which has a dipole moment of 1.84 Debye, into the conjugated backbone of polymer donors to fabricate high-efficiency OSCs from anisole, a real green and eco-compatible solvent recommended by the United Nations. Based on a newly developed B–N-based polymer, the OSCs with a record-high efficiency of 15.65% in the 0.04 cm 2 device and 14.01% in the 1.10 cm 2 device have thus been realized via real green processing.